Design of Application of Raw Material Control at PT Kasa Husada Wira Jatim - Rochmawati, Dian; Arifin, Mochammad; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
PT Kasa Husada Wira Jatim is a manufacturing company engaged in the manufacture of various health purposes such as gauze, sanitary napkins, and cotton. Currently on the company there is no process of controlling the raw materials in particular so as to make the company often experience shortages of raw materials at the time will make the production process orders from customers. The above problems required an application of raw material inventory control using Economic Order Quantity to provide the quantity of raw materials must be purchased at a certain period for a minimum fee. And then calculate the Safety Stock to determine the amount of safety stock by comparing the use of raw materials which will then be searched for standard deviation value. The last step is to calculate Reorder Point to find out the value of re-ordering point of raw material at the company. Test result, design of raw material control application yield five reports. The resulting report is customer order report, raw material receipt report, raw material expenditure report, raw material inventory report, and production report. Of the five reports can be used as a reference company in controlling raw materials.Keywords: Application of raw material control, Economic Order Quantity, Safety Stock, Reorder Point.